The Pontastacus leptodactylus (Astacidae) Repeatome Provides Insight Into Genome Evolution and Reveals Remarkable Diversity of Satellite DNA - Boštjančić, Ljudevit Luka; Bonassin, Lena; Anušić, Lucija; Lovrenčić, Leona; Besendorfer, Višnja; Maguire, Ivana; Grandjean, Frederic; Austin, Christopher M.; Greve, Carola; Hamadou, Alexander Ben; Mlinarec, Jelena (Frontiers in Genetics, 2021)
Pontastacus leptodactylus is a native European crayfish species found in both freshwater and brackish environments. It has commercial importance for fisheries and aquaculture industries. Up till now, most studies concerning P. leptodactylus have focused onto gaining knowledge about its phylogeny and population genetics. However, little is known about the chromosomal evolution and genome organization of this species. Therefore, we performed clustering analysis of a low coverage genomic dataset to identify and characterize repetitive DNA in the P. leptodactylus genome. In addition, the karyogram of P. leptodactylus (2n = 180) is presented here for the first time consisting of 75 metacentric, 14 submetacentric, and a submetacentric/metacentric heteromorphic chromosome pair. We determined the genome size to be at 18.7 gigabase pairs. Repetitive DNA represents about 54.85% of the genome. Satellite DNA repeats are the most abundant type of repetitive DNA, making up to 28% of the total amount of repetitive elements, followed by the Ty3/Gypsy retroelements ( 15%). Our study established a surprisingly high diversity of satellite repeats in P. leptodactylus. The genome of P. leptodactylus is by far the most satellite-rich genome discovered to date with 258 satellite families described. Of the five mapped satellite DNA families on chromosomes, PlSAT3-411 co-localizes with the AT-rich DAPI positive probable (peri)centromeric heterochromatin on all chromosomes, while PlSAT14-79 co-localizes with the AT-rich DAPI positive (peri)centromeric heterochromatin on one chromosome and is also located subterminally and intercalary on some chromosomes. PlSAT1-21 is located intercalary in the vicinity of the (peri)centromeric heterochromatin on some chromosomes, while PlSAT6-70 and PlSAT7-134 are located intercalary on some P. leptodactylus chromosomes. The FISH results reveal amplification of interstitial telomeric repeats (ITRs) in P. leptodactylus. The prevalence of repetitive elements, especially the satellite DNA repeats, may have provided a driving force for the evolution of the P. leptodactylus genome.